Creating Noble Morals through the Al-Quran Education Park in Ciberes Village - M. Ibnu Muzakir (Universitas Darunnajah, Jakarta, Indonesia, 2023)
AbstractWith the decline in morals towards children today, it is necessary to get gentle educational touches from both parents, without using physical or psychological violence in order to create future generations of Muslims who have noble morals.